Technological Gap in Adoption of Recommended Wheat Production Practices (Indian Journal of Extension Education, 2011)
Wheat is the main rabi crop growing in Vindhyan Plateau of Madhya Pradesh and Sehore is one of the major wheat growing area in the plateau. The technological development in agriculture increased the production and productivity but the impact of improved wheat production practices has not been so prominent in some area of Madhya Pradesh particularly in traditional practicing areas. In wheat growing area of Madhya Pradesh the technological change have been found in wide scale but the growth of wheat production in wheat growing area has been very slow mainly due to traditional nature of farming dominated by rainfed wheat production situation resulted very low level of productivity.